Color speckle assessment for laser projection systems based on human speckle perception. (December 2022) - Deng, Linxiao; Yang, Yuhua; Wang, Guan; Yao, Binghui; Ma, Jiafei; Zhu, Liquan; Gu, Chun; Xu, Lixin
Highlights: Standardized color speckle measurement method replicating human eye functions. Irregular spectrum distribution based on a practical laser projection system. Experimental verification implemented with a complete laser projector. Abstract: Laser displays are commonly used in various applications. However, they are subject to the color speckle phenomenon. Herein, a color speckle measurement method for laser projection systems based on human speckle perception was developed. This method was based on the practical irregular spectrum distribution of a laser projection system. The proposed numerical calculation was more aligned with the speckle of practical systems than the monochromatic light approximation in previous literatures. Additionally, the key parameters of the measurement configuration were provided, which were based on human eye characteristics. Experimental verification was implemented with a complete laser projector. The proposed method can therefore serve as a basis for standardized color speckle measurement applications in laser projection systems.